"El Dean de Canterbury en Badalona, palabras del Alcalde". From the left: Montseny, Souchy, the Dean. Copied from CNT collection
"El Dean de Canterbury en Badalona, palabras del Alcalde". From the left: Montseny, Souchy, the Dean. Copied from CNT collection.